Morphing airfoils analysis using dynamic meshing. Issue 5 (8th May 2018) - Abdessemed, Chawki; Yao, Yufeng; Bouferrouk, Abdessalem; Narayan, Pritesh
Abstract : Purpose: The purpose of this paper is to use dynamic meshing to perform CFD analyses of a NACA 0012 airfoil fitted with a morphing trailing edge (TE) flap when it undergoes static and time-dependent morphing. The steady CFD predictions of the original and morphing airfoils are validated against published data. The study also investigates an airfoil with a hinged TE flap for aerodynamic performance comparison. The study further extends to an unsteady CFD analysis of a dynamically morphing TE flap for proof-of-concept and also to realise its potential for future applications. Design/methodology/approach: An existing parametrization method was modified and implemented in a user-defined function (UDF) to perform dynamic meshing which is essential for morphing airfoil unsteady simulations. The results from the deformed mesh were verified to ensure the validity of the adopted mesh deformation method. ANSYS Fluent software was used to perform steady and unsteady analysis and the results were compared with computational predictions. Findings: Steady computational results are in good agreement with those from OpenFOAM for a non-morphing airfoil and for a morphed airfoil with a maximum TE deflection equal to 5 per cent of the chord. The results obtained by ANSYS Fluent show that an average of 6.5 per cent increase in lift-to-drag ratio is achieved, compared with a hinged flap airfoil with the same TE deflection. By using dynamic meshing, unsteady transient simulations reveal that the local flow field is influenced by the morphing motion. Originality/value: An airfoil parametrisation method was modified to introduce time-dependent morphing and used to drive dynamic meshing through an in-house-developed UDF. The morphed airfoil's superior aerodynamic performance was demonstrated in comparison with traditional hinged TE flap. A methodology was developed to perform unsteady transient analysis of a morphing airfoil at high angles of attack beyond stall and to compare with published data. Unsteady predictions have shown signs of rich flow features, paving the way for further research into the effects of a dynamic flap on the flow physics.